A METHOD FOR RESTORING ORAL CAVITY AND TONGUE USING A COMPOSITE, FREE, CHIMERIC, REVASCULARIZED, REINNERVED, MUSCULOCUTANEOUS FLAP AFTER TOTAL GLOSSECTOMY - A. P. Polyakov; A. D. Kaprin; M. V. Ratushnyy; O. V. Matorin; I. V. Rebrikova; M. M. Filyushin; A. V. Mordovskiy; P. A. Nikiforovich (Опухоли головы и шеи)
Background. Combination therapy is the main method used for treatment of patients with locally advanced cancer of the oral floor and tongue. Radical surgery is a key stage of this therapy. These surgeries are inevitably associated with extensive defects in the oral cavity and tongue and, therefore, the loss of necessary organism functions. Currently, there is no optimal autotransplant for tongue reconstruction after total or subtotal removal of the tongue and oral floor muscles; it appears to be one of the most significant challenges in modern reconstructive surgery.Materials and methods. The authors describe a case of successful repair of the oral floor and tongue after total glossectomy using a novel method developed in the Department of Microsurgery at the P. A. Herzen Moscow Oncology Research Institute – branch of the National Medical Research Radiology Center, Ministry of Health of Russia. This method implies tongue reconstruction using a revascularized, reinnerved, chimeric, thoracodorsal flap with inclusion of a muscular portion from the serratus anterior muscle and a musculocutaneous portion from the latissimus dorsi muscle. We performed tongue reconstruction in a 62-year-old patient diagnosed with stage IVA (Т3N2bМ0) tongue cancer. Results. The novel method of surgical treatment of locally advanced tongue cancer with simultaneous repair of defects using a revascularized, reinnerved, chimeric flap with inclusion of the serratus anterior muscle and latissimus dorsi muscle allowed to remove the tumor, stabilize the laryngeal complex, restore the diaphragm of the oral floor, create an adequate volume of neotongue, obtain good functional and cosmetic results, and reduce the length of hospital stay. Conclusion. Novel method of surgical treatment of locally advanced tongue cancer facilitates health, employment, and social rehabilitation of patients with oropharyngeal cancer. This method can be considered as an alternative method of choice in the reconstruction of complex post-traumatic oropharyngeal defects.